2019
DOI: 10.1186/s12885-019-5529-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered profile of immune regulatory cells in the peripheral blood of lymphoma patients

Abstract: Background Regulatory immune cells may modulate the lymphoma microenvironment and are of great interest due to the increasing prevalence of treatment with immunotherapies in lymphoma patients. The aim was to explore the composition of different immune regulatory cell subsets in the peripheral blood of newly diagnosed lymphoma patients in relation to treatment outcome. Methods Forty-three newly diagnosed patients with lymphoma were included in the study; 24 with high-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…Our group showed that three MDSCs subtypes, including CD14+HLA-DR-mo-MDSCs, were increased in newly-diagnosed advanced-stage HL patients and reduced after two and six cycles of ABVD chemotherapy [20]; similarly, in relapsed/refractory patients, several MDSCs subtypes, including mo-MDSCs, were increased at time of disease progression and reduced after treatment with brentuximab vedotin [19]. However, immune-suppressive effect and correlation with outcome is stronger for g-MDSCs than mo-MDSCs in HL [20,38,39]. Another study demonstrated that g-MDSCs were increased in both HL and B-cell NHL patients and correlated significantly with unfavorable prognostic index scores and an inferior outcome [38].…”
Section: Monocytic Myeloid Derived Suppressor Cells In Hodgkin Lymmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group showed that three MDSCs subtypes, including CD14+HLA-DR-mo-MDSCs, were increased in newly-diagnosed advanced-stage HL patients and reduced after two and six cycles of ABVD chemotherapy [20]; similarly, in relapsed/refractory patients, several MDSCs subtypes, including mo-MDSCs, were increased at time of disease progression and reduced after treatment with brentuximab vedotin [19]. However, immune-suppressive effect and correlation with outcome is stronger for g-MDSCs than mo-MDSCs in HL [20,38,39]. Another study demonstrated that g-MDSCs were increased in both HL and B-cell NHL patients and correlated significantly with unfavorable prognostic index scores and an inferior outcome [38].…”
Section: Monocytic Myeloid Derived Suppressor Cells In Hodgkin Lymmentioning
confidence: 99%
“…Another study demonstrated that g-MDSCs were increased in both HL and B-cell NHL patients and correlated significantly with unfavorable prognostic index scores and an inferior outcome [38]. In a third small series, only g-MDSCs (but not mo-MDSCs) were increased in HL patients compared to healthy controls [39].…”
Section: Monocytic Myeloid Derived Suppressor Cells In Hodgkin Lymmentioning
confidence: 99%
“…Patients received neither immunosuppressive therapy nor chemotherapy for at least 3 months; thus, the percentages seem to reflect their constant immune status. In contrast to this, a recent study has compared proportions of suppressor cell subpopulations in lymphoma patients (n = 43) and healthy donors [100]. No significant difference in Treg populations between the groups was observed, although some non-T-cell populations (MDSC and NK regulatory cells) were elevated in the patients.…”
Section: Treg Subsets May Be Overrepresented In Peripheral Blood Of Pmentioning
confidence: 90%
“…No significant difference in Treg populations between the groups was observed, although some non-T-cell populations (MDSC and NK regulatory cells) were elevated in the patients. The above-studied cohorts were similar (Europeans,~60 years), however direct comparison of the results cannot be totally correct due to variations in applied methodology: (1) calculation of Treg percentages in total population of PBMCs [100] or blood cells [99]; and (2) different definition of Treg phenotypes. Some studies on lymphoma patients have similarly found no variation in Treg levels in comparison to healthy volunteers [101,102], while others reported several-fold difference regardless of nationality, age and disease status (newly diagnosed vs. relapsed) [102][103][104].…”
Section: Treg Subsets May Be Overrepresented In Peripheral Blood Of Pmentioning
confidence: 99%
“…This could be linked to an increase in monocytic myeloid derived suppressor cells (M-MDSC), as it has been suggested in DLBCL ( 20 , 31 ) and CLL, in which M-MDSC levels correlate with response to treatment ( 32 35 ). Concerning the granulocytic lineage, polymorphonuclear MDSC (PMN-MDSC) have been proposed as a marker of poor prognosis in DLBCL ( 36 ), but other works did not find any association between PMN-MDSC and DLBCL prognosis ( 31 , 37 ). In HL, the presence of a CD34 pos MDSC subtype in the blood has been associated with worsened prognosis ( 38 ).…”
Section: Introductionmentioning
confidence: 99%